Evaluation of complicated and uncomplicated parapneumonic effusion in children - Gayretli-Aydın, Zeynep Gökçe; Tanır, Gönül; Bayhan, Gülsüm İclal and Aydın-Teke, Türkan and Öz, Fatma Nur and Metin-Akcan, Özge and Kaman, Ayşe (The Turkish Journal of Pediatrics, 2016)
Parapneumonic effusion (PPE) and empyema are most often seen as a complication of bacterial pneumonia and occasionally associated with atypical bacteria or viruses. The aims of this study were to describe and compare demographic characteristics, clinical, laboratory, microbiological findings and treatment modalities of patients with PPE and empyema. We retrospectively reviewed 116 pediatric patients with PPE and empyema. Seventy (60.3%) had pleural empyema and 46 patients (39.6%) had PPE. The median age of patients with empyema [72.0 months (IQR 68.0 months)] was lower than the patients with PPE [92.5 (IQR 80.0 months)] (p=0.003). Children in the empyema group had significantly more dyspnea symptoms than the children with PPE (p=0.022). Mean fever duration before hospitalization was similar in both groups. Streptococcus pneumoniae and group A streptococcus were the most common causes of empyema. All of the patients were treated with intravenous antibiotics. In addition to medical treatment, tube thoracostomy was performed in 59 of 70 (84.3%) patients in empyema group; 27 (45.8%) of them required intrapleural fibrinolysis also. In the presence of antibiotic treatment failure or in cases with moderate or large pleural effusion with loculations and clinical deterioration; it is necessary to perform drainage of the purulent fluid by tube thoracostomy, to add intrapleural fibrinolytics or to perform video-assisted thoracoscopic surgery (VATS), in order to enhance prompt recovery.